Knowledge, attitudes, and practices regarding floaters among patients - Bin Zhang; Bin Zhang; Hangyu Liu; Haijing Zhu; Xianyong Sun; Xianyong Sun; Rongyu Gao; Rongyu Gao (Frontiers in Medicine)
ObjectivesThis study aimed to investigate the knowledge, attitudes, and practices (KAP) regarding floaters among patients with floaters.MethodsThis cross-sectional study enrolled participants diagnosed with floaters between April 2023 and October 2023 in Weifang, China. Demographic information and KAP regarding floaters were collected via web-based questionnaires.ResultsA total of 430 respondents were included, with 251 (58.37%) females. Of the respondents, 270 (62.79%) experienced their first episode of floaters for less than 1 year. Mean knowledge, attitude, and practice scores were 8.81 ± 4.20 (possible range: 0–13), 17.23 ± 5.05 (possible range: 6–30), and 14.67 ± 2.95 (possible range: 4–20), respectively. Correlation analyses revealed a significant positive relationship between knowledge and practices (r = 0.239, p < 0.001), whereas attitudes were inversely associated with practices (r = −0.219, p < 0.001). The structural equation model revealed that knowledge had a direct positive influence on practices (β = 0.403, p < 0.001), while attitudes exhibited a direct negative impact on practices (β = −0.112, p < 0.001).ConclusionPatients demonstrated suboptimal knowledge and negative attitudes, but many engaged in proactive practices to manage floaters. Interventions focusing on enhancing knowledge and fostering positive attitudes among individuals with floaters are recommended to improve clinical practices.